2018
DOI: 10.1002/jpln.201700531
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of rapeseed (Brassica napus) cultivars for potential higher and lower Cd accumulation

Abstract: Cadmium (Cd) as a non-essential toxic metal has become one of the seriously environmental problems. Overload of Cd into plant shoots, particularly the addible parts (i.e., grains), jeopardizes crop production and food safety. Isolating and identifying genotypic variations in Cd accumulation of rapeseed (Brassica napus) cultivars is an efficient approach for phytoremediation and developing lower Cd-accumulating plants. In this study, a trial was conducted under natural condition in Nanjing, China, from 2014 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Measuring Cd concentration in 69 rice accessions, Uraguchi et al (2009b) found strong correlations between Cd levels in the xylem sap and in shoots and grains. Zhang et al (2018) obtained similar results in the case of rape (B. napus). Harris and Taylor (2013) demonstrated the importance of root-to-shoot translocation in the accumulation of Cd in durum wheat grain.…”
Section: B Transport In the Xylemsupporting
confidence: 59%
“…Measuring Cd concentration in 69 rice accessions, Uraguchi et al (2009b) found strong correlations between Cd levels in the xylem sap and in shoots and grains. Zhang et al (2018) obtained similar results in the case of rape (B. napus). Harris and Taylor (2013) demonstrated the importance of root-to-shoot translocation in the accumulation of Cd in durum wheat grain.…”
Section: B Transport In the Xylemsupporting
confidence: 59%
“…Studies have shown that rapeseed was regarded as a high Cd-accumulating plant mainly due to the high accumulation of Cd in nonedible parts. , As this study and other previous study of Yang et al have shown, the seed meal sequestrated Cd. Hence, only a significant small fraction of Cd was transferred to the oil (0.8% of the Cd in shoots).…”
Section: Resultssupporting
confidence: 70%
“…Oilseed rape (Brassica napus L.) is one of the staple oil crops in China and Europe with strong Cd accumulation , in no-edible parts . The characteristics of oilseed rape make it a good candidate for soil Cd remediation. , The main economic value of rapeseed comes from rapeseed oil extraction, and the large biomass of oilseed rape may be used for ethanol, biochar, and biofuel production by hydrolysis, pyrolysis, and fermentation. , It is important to evaluate the risk of Cd in oil and seed meal, especially from heavily polluted farmlands.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperaccumulators can be used for phytoremediation and also for phytomining [4,14,15,16]. Phytoremediation is a cost-effective and environmentally-friendly technology that uses plants to remove the toxic metals from soils; it has been widely used in practice [14,17].…”
Section: Introductionmentioning
confidence: 99%